2022
DOI: 10.1021/acschemneuro.1c00523
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin and Bacillus Calmette–Guérin Vaccination Mitigate 3-Nitropropionic Acid-Induced Huntington-like Disease in Rats by Modulating the PI3K/Akt/mTOR/P70S6K Pathway and Enhancing the Autophagy

Abstract: Oxidative stress and mitochondrial dysfunction are among the mechanisms expected to explain the pathogenesis of Huntington's disease. Erythropoietin (EPO) and the Bacillus Calmette−Gueŕin (BCG) vaccine have neuroprotective effects against neurodegenerative diseases; however, the full mechanisms of their action are currently unclear. Here, for the first time, we investigated the neuroprotective effect of BCG vaccination in Huntington-like disease induced by 3-nitropropionic acid (3-NP) and its combination with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 76 publications
1
14
0
Order By: Relevance
“…Oxidative stress and mitochondrial dysfunction have an impeccable role in the pathogenesis of neurodegenerative diseases, including PD, , orchestrating the production of ROS that advances the ER stress magnitude . As displayed by our results, the intoxicated rats demonstrated impairment of mitophagy verified by the downregulated PINK1 expression concomitant with a marked decrease in the activity of the antioxidant catalase.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Oxidative stress and mitochondrial dysfunction have an impeccable role in the pathogenesis of neurodegenerative diseases, including PD, , orchestrating the production of ROS that advances the ER stress magnitude . As displayed by our results, the intoxicated rats demonstrated impairment of mitophagy verified by the downregulated PINK1 expression concomitant with a marked decrease in the activity of the antioxidant catalase.…”
Section: Resultssupporting
confidence: 59%
“…Recently, our group and others have uncovered multiple therapeutic targets for the treatment of neurodegenerative diseases. ,,, Notably, a rising number of studies suggest that focusing on ER stress in treating neurodegeneration is a feasible therapeutic approach to PD. ,, An earlier work done on IRE1α knockout PD mice model highlighted the chief role of mesencephalic astrocyte-derived neurotrophic factor in mitigating ER stress. By directly binding to IRE1α, it augments UPR and as a result preserves the count of viable dopamine neurons .…”
Section: Resultsmentioning
confidence: 99%
“…As the same, the secretions of VEGF-a, FGF-2, and IGF-1 were declined with the increasing concentration of TNF-α, which denoted the decreasing angiogenic level. Taken together, autophagy impaired by TNF-α was considered as a protective factor researches argued that EPO attenuated inflammation, contributed to antiapoptosis, enhanced autophagy, and promoted angiogenesis [13,18,[57][58][59]. Meanwhile, some researches [60][61][62] supported that EPO receptor (EPOR) was expressed in many CD105 + /CD90 + /CD44 + stem cells-such as PDLSCs, dental pulp stem cells, and bone marrow progenitor cells-which demonstrated that the EPO/EPOR signaling pathway played a crucial role in regulating biological behaviors of these cells.…”
Section: Discussionmentioning
confidence: 99%
“…EPO has been learned as a multifunctional cytokine/drug for wound healing and bone regeneration, particularly in the realm of periodontology [ 54 56 ]. An avalanche of researches argued that EPO attenuated inflammation, contributed to antiapoptosis, enhanced autophagy, and promoted angiogenesis [ 13 , 18 , 57 59 ]. Meanwhile, some researches [ 60 62 ] supported that EPO receptor (EPOR) was expressed in many CD105 + /CD90 + /CD44 + stem cells—such as PDLSCs, dental pulp stem cells, and bone marrow progenitor cells—which demonstrated that the EPO/EPOR signaling pathway played a crucial role in regulating biological behaviors of these cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation